lncRNA/miR-29c-Mediated High Expression of LOX Can Influence the Immune Status and Chemosensitivity and Can Forecast the Poor Prognosis of Gastric Cancer - Nai, Aitao; Zeng, Huihui; Wu, Qiong; He, Zirui; Zeng, Shuwen; Bashir, Shoaib; Ma, Feng; He, Jie; Wan, Wei; Xu, Meng (Frontiers in Cell and Developmental Biology, 2022)
Gastric carcinoma is the fourth most prevalent cause of cancer-related death worldwide because of dismal prognosis and few therapeutic options. Accumulated studies have indicated that targeting LOX family members may serve as an anticancer strategy. Nevertheless, the specific mechanisms of LOX in stomach carcinoma are still unclear. In this study, we demonstrated that the expression LOX is significant difference in 13 types of cancers, and may act as a potential therapeutic target, especially stomach carcinoma. Moreover, overexpression of LOX in gastric carcinoma was validated by multiple databases, and contributed to the poor OS, PFS and PPS of STAD patients. Next, based on the ceRNA hypothesis, HIF1A-AS2/RP11-366L20.2-miR-29c axis was characterized as the upstream regulatory mechanism of LOX gene overexpression in gastric cancer by combining with correlation analysis, expression analysis and survival analysis. Finally, we illustrated that LOX gene overexpression leads to dismal prognostic of gastric cancer, perhaps through promoting M2 macrophage polarization and tumor immune escape and enhancing drug resistance of tumor cells to chemotherapy drugs. Our research demonstrate that LOX may be potentially applied as a novel prognostic marker and targeting inhibition of LOX holds promise as a treatment strategy for gastric cancer.